Prevalence of HCV Infection in Hemodialysis Patients of South Khorasan in Comparison With HBV, HDV, HTLV I/II, And HIV Infection (Bangladesh Journal of Medical Science, 2013)
Background and objective: This study was performed to evaluate the prevalence of Hepatitis C virus (HCV) infection as well as HBV, HDV, HTLV I/II, and HIV infection in hemodialysis patients in our district. Methods: The subjects of this study involved 41 hemodialysis patients admitted to hemodialysis ward, Vali- Asr hospital. HBV, HDV, HIV, and HTLV1/2 infections were evaluated by enzyme-linked immunosorbent assay (ELISA) technique. Serum anti- HCV anti-body was measured using the 3rd generation of ELISA kit. HCV Viremia was evaluated in all patients using RT-PCR technique. Results: HCV infection was not observed in none of patients by ELISA technique; however RT-PCR technique demonstrated HCV viremia in one (2.43%) patient. HBsAg was detected in 4(9.75%) patients, and one (2.43%) was Anti HTLV 1/2 positive; none of patients were HDV or HIV positive. Conclusion: HCV infection is less common than HBV infection in our patients. ELISA technique can not demonstrate all hemodialysis patients with HCV infection, For this reason it is requirement to evaluate this group of patients for HCV infection using RT-PC technique. DOI: http://dx.doi.org/10.3329/bjms.v13i1.13903 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 36-39